Tópoi elegíacos nas Heroides de Ovídio - Wilker Pinheiro Cordeiro (2013)
The poet Publius Ovidius Naso (43 b. C. - 17 a. D.) began his literary career early, singing themes highly appreciated by the youth, such as love, seduction and good living. And the style that best conveyed those themes was the love elegy, inspired from Alexandrian writers such as Callimachus and the previous generation of Latin poets, especially Tibullus, Propertius, Cornelius Gallus, and Catullus. Later, Ovid expanded both the theme and variety of the genres he wrote. The goal of this work is to verify the presence of motifs (tópoi) typically elegiac in the poems IV, V, VI, IX, XI and XII of the Heroides, an Ovid work comprising eighteen fictional letters from epic heroines to their absent beloved ones and the corresponding responses to three of them. Finally, it is also proposed a commented translation of such poems, a general study on love elegy, and their most recurring tópoi.